Student-centered teacher responses to student behavior in the classroom: A systematic review - Karasova, Jirina; Nehyba, Jan (Frontiers in Education, 2023)
Effective communication skills are a key component of successful behavior management in the classroom. Teachers who can respond to student behavior in a proactive, student-centered manner create a positive and productive learning environment. However, despite its importance, the empirical support for student-centered communication practices in behavior management is limited. This study aims to fill that gap by identifying the characteristics of these strategies that lead to lower behavior problems and increased engagement among students. Through a systematic literature review, this study found five main categories that characterize student-centered behavior management responses and presents a table of 24 communication strategies identified throughout the review. Additionally, the study also discussed the further impact of these strategies on student motivation, learning outcomes, responsibility and interpersonal classroom climate. These findings highlight the importance of effective communication skills in behavior management and provide valuable insights for teachers to improve their practice.